Morphology of Setaria spp. (Setariidae; Nematoda) in Aceh cattle, Indonesia - MUHAMMAD HANAFIAH; FARIDA ATHAILLAH; T. ZAHRIAL HELMI; AMALIA SUTRIANA (Society for Indonesian Biodiversity, 2023)
Abstract. Hanafiah M, Athaillah F, Helmi TZ, Sutriana A. 2023. Morphology of Setaria spp. (Setariidae; Nematoda) in Aceh cattle, Indonesia. Biodiversitas 24: 4151-4160. Setaria spp. filaria usually inhabit the peritoneal cavity and its microfilaria can be found in cattle blood. Adult worms are considered non-pathogenic but may cause mild fibrinous peritonitis. However, microfilaria can cause serious conditions. The worms migrate randomly to the central nervous system in a non-natural host such as sheep, horses, and goats, causing serious neuropathological symptoms which are known as epizootic cerebrospinal setariosis or nematodiasis cerebrospinal. The objective of this research was to determine the prevalence of Setaria spp. microfilaria in the blood of infected Aceh cattle, identify the worm species in the peritoneal cavity, and determine the morphological difference of Setaria spp. through light microscope (LM) and Scanning Electron Microscope (SEM). This research was performed on 150 Aceh cattle slaughtered in Banda Aceh slaughterhouse. The hematocrit microcapillary method and modified Knott’s Technique were used to determine the presence of Setaria spp. microfilaria in blood, while LM and SEM were used to identify Setaria spp. adult worm. The results showed that Setaria spp. was detected in Aceh cattle blood based on modified Knott’s Technique and hematocrit microcapillary method with a similar prevalence of 13.3%. The worm identification revealed the presence of Setaria spp. in the peritoneal cavity of Aceh cattle. The morphological differences between Setaria digitata and Setaria labiatopapillosa were successfully discovered through LM and SEM studies.